Fyke Farmer papers - Farmer, Fyke.
Correspondence, court documents and legal papers, speech material, writings, notes, press clippings, journal articles, and other material relating chiefly to Farmer's legal work and interest in the espionage case of Julius and Ethel Rosenberg. Includes documents concerning other accused spies David Greenglass and Morton Sobell and files pertaining to Farmer's law suit (United States ex rel. Farmer v. Kaufman) in 1990 against Irving R. Kaufman, the judge who presided over the Rosenbergs' trial. Also documents Farmer's endeavors to create a "one world government," advocacy for international control of atomic energy, and law suit against the Internal Revenue Service defending his refusal to pay federal income tax based on the argument that the Korean War was illegal. Correspondents include Ethel Rosenberg Appel, Emanuel H. Bloch, Irwin Edelman, Dwight D. Eisenhower, Marshall Perlin, and Norman A. Plotkin.
Lawyer and activist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Appel, Ethel Rosenberg -- Correspondence; Bloch, Emanuel H. -- Correspondence; Edelman, Irwin -- Correspondence; Eisenhower, Dwight D. -- 1890-1969 -- Correspondence; Greenglass, David, -- 1922- -- Trials, litigation, etc; Kaufman, Irving R. -- 1910-1992 -- Trials, litigation, etc; Perlin, Marshall, -- 1920-1998 -- Correspondence; Plotkin, Norman A. -- Correspondence; Rosenberg, Ethel, -- 1915-1953 -- Trials, litigation, etc; Rosenberg, Julius, -- 1918-1953 -- Trials, litigation, etc; Sobell, Morton -- Trials, litigation, etc; Income tax -- United States; International organization; Nuclear energy -- International cooperation; Trials (Espionage) -- New York (State) -- New York; Trials (Conspiracy) -- New York (State) -- New York; Lawyers